2020
DOI: 10.1093/jncics/pkaa047
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persistence of Oral HPV Over 7 Years of Follow-up

Abstract: Background HPV-related oropharyngeal cancer (HPV-OPC) incidence is increasing but the natural history of the precursor, oral HPV, has not been well described. Methods This observational cohort study of people living with HIV and at-risk HIV uninfected people evaluated participants semi-annually using 30-second oral rinse/gargle specimens over 7 years. Initially, 447 subjects were followed for four years as part of the POPS St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 35 publications
(43 reference statements)
3
45
0
Order By: Relevance
“…Salivary HR-HPV positivity at the very early stages of HNC has also been proven in two recent studies in which longitudinal salivary HPV testing was coupled with clinical investigations to detect HNC in asymptomatic individuals. 13,14 These studies, together with the present findings, highlight the possible utility of screening programs based on longitudinal salivary HR-HPV DNA testing for the early detection of HPV-HNC. Furthermore, the present findings indicate the potential of salivary HR-HPV DNA testing for HNC patient monitoring.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Salivary HR-HPV positivity at the very early stages of HNC has also been proven in two recent studies in which longitudinal salivary HPV testing was coupled with clinical investigations to detect HNC in asymptomatic individuals. 13,14 These studies, together with the present findings, highlight the possible utility of screening programs based on longitudinal salivary HR-HPV DNA testing for the early detection of HPV-HNC. Furthermore, the present findings indicate the potential of salivary HR-HPV DNA testing for HNC patient monitoring.…”
Section: Discussionsupporting
confidence: 66%
“…This hypothesis is attested to in two recent studies in which it was confirmed that longitudinal salivary HR-HPV testing, coupled with clinical investigations, identified HPV-HNC in asymptomatic individuals. 13,14 However, varying degrees of sensitivity of salivary HPV detection in HPV-HNC patients have been reported. 15e20 A general consensus, therefore, has not been reached regarding the utility of HPV detection for HPV-HNC identification and monitoring.…”
mentioning
confidence: 99%
“…HPV infections may remain asymptomatic or may be detected as wart-like oral lesions, with most HPV oral infections tend to clear within 18 months [ 8 ]. However, a small percentage of HPV oral infections may persist for a longer period of time and transform into malignant lesion, particularly the high risk of HPV oral infections that are linked to HPV types 16 and 18 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After surgical excision of the clinically occult 2 mm tonsillar HPV-OPC, HPV DNA became undetectable in saliva. A further report of persistent oral HPV 16 infection with incident diagnosis of HPV-OPC also demonstrated a rise in oral HPV 16 from low to high intensity, prior to the diagnosis of an invasive malignancy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%